9. KNOWLEDGE AND PRACTICE OF ADHERENCE IN PATIENTS WITH BASEDOW AT THE THYROID CLINIC OF 108 MILITARY CENTRAL HOSPITAL AND RELATED FACTORS IN 2022 (Vietnam Journal of Community Medicine, 2022)
Objectives: To describe the current status of knowledge and adherence practice in patients withBasedow at the thyroid clinic of 108 Military Central Hospital and related factors.Materials and methods: It is a cross-sectional study in that all patients were definitively diagnosedwith Basedow. They were treated as outpatients at the clinic for Thyroid diseases, 108 MilitaryCentral Hospital, in 2022.Results: The percentage of patients with knowledge and practice of treatment adherence was 57.07%and 55.83%, respectively. Various factors, including education level, occupation, family status andgeographic location, and distance from home to the hospital, were all related to knowledge andpractice of adherence in treatment.Conclusion: There are differences in knowledge and practice of adherence across age groups,education levels, occupations and geographical locations.
Keywords: Knowledge; practice; treatment adherence; Basedow; outpatients.